A new evaluation of masticatory ability in patients with dysphagia: The Saku-Saku Test. (January 2018) - Tagashira, I.; Tohara, H.; Wakasugi, Y.; Hara, K.; Nakane, A.; Yamazaki, Y.; Matsubara, M.; Minakuchi, S.
Graphical abstract: Highlights: We used the SST to assess the chewing and swallowing ability in dysphagic patients. In the SST, the mandibular rotation during chewing was evaluated. The SST showed good reliability between examiners. The SST is useful to identify masticatory function in dysphagic patients. Abstract: Objective: In the elderly and patients with dysphagia, masticatory problems often cause aspiration or choking. Although simple methods to predict aspiration and silent aspiration exist, methods for evaluating the masticatory function of patients with dysphagia are lacking. Accordingly, we developed a simple test to assess the chewing and swallowing ability of patients with dysphagia. Methods: One hundred and five patients with dysphagia were included. We used the Saku-Saku Test (SST), in which patients were asked to eat a rice cracker, and evaluated the quality of mandibular rotation during mastication. We studied the participants' ability to grind, aggregate, and swallow using videoendoscopic evaluation (VE) and investigated its association with mandibular rotation. Results: The SST showed good reliability between two examiners, with a kappa coefficient of 0.80. 92.4% of the patients ate the rice cracker without aspiration. The SST showed a high sensitivity of 73.3% and specificity of 93.3% for the degree of grinding. The degree of food bolus aggregation had a sensitivity of 45.0% and specificity of 90.6%, and aspiration had a sensitivity of 25.0% and specificity of 84.5%, both of which showed high specificity. Conclusions: The results of this study suggested that the SST might be simple and useful for identifying patients with dysphagia who are able to masticate, even if they do not eat foods that need chewing and could be used before starting these patients on foods that need chewing.